Utilization of rice, mungbean and malunggay in hamburger patties by - Magdale, Rosebelle N.
Rice flour, mungbean and malunggay were utilized to partially replace meat in hamburger patties. Mungbean was used in different forms: boiled, sprouts and flour, which were mixed with rice flour in a ratio of 3:7. The rice-mungbean mixture was used to partially replace the meat in hamburger pattie at 40, 50, and 60% substitution. Malunggay and TVP were added at fixed rates of 1% and 30% respectively. Twenty-four consumer panelists evaluated the products, together with a commercial sample, for overall appearance, flavor, texture and general acceptability. Samples that received ratings of 5.0 or greater were considered to be acceptable to the consumers. Results showed that hamburger patties the meat of which was substituted with 50% rice flour-mungbean sprout mixture or with 50% rice flour-boiled mungbean mixture was acceptable to the consumers. Rice flour-mungbean flour mixturs were not good substitutes for meat in hamburger pattie because products made from these mixtures were not acceptable to consumers.